2020
DOI: 10.1038/s41396-020-0721-4
|View full text |Cite
|
Sign up to set email alerts
|

A spore quality–quantity tradeoff favors diverse sporulation strategies in Bacillus subtilis

Abstract: Quality–quantity tradeoffs govern the production of propagules across taxa and can explain variability in life-history traits in higher organisms. A quality–quantity tradeoff was recently discovered in spore forming bacteria, but whether it impacts fitness is unclear. Here we show both theoretically and experimentally that the nutrient supply during spore revival determines the fitness advantage associated with different sporulation behaviors in Bacillus subtilis. By tuning sporulation rates we generate spore-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 61 publications
1
29
0
5
Order By: Relevance
“…As has been also shown recently, there is a trade-off between spore quantity and quality in B. subtilis ( 57 , 58 ). The results of our measurements of AP activity and DPA content as markers for sporulation stages II/III and IV/V, respectively, revealed that the absence of SR1 restricts the time window of spore formation to an extent that prevents the assembly of a proper coat and crust.…”
Section: Discussionmentioning
confidence: 52%
“…As has been also shown recently, there is a trade-off between spore quantity and quality in B. subtilis ( 57 , 58 ). The results of our measurements of AP activity and DPA content as markers for sporulation stages II/III and IV/V, respectively, revealed that the absence of SR1 restricts the time window of spore formation to an extent that prevents the assembly of a proper coat and crust.…”
Section: Discussionmentioning
confidence: 52%
“…Trotzdem wurden diese bisher getrennt voneinander untersucht. Die Lichtmikroskopie ist dafür ein wichtiges Werkzeug, denn die verschiedenen Entwicklungs- [6].…”
Section: Der Lebenszyklus Im Zeitrafferunclassified
“…Korreliert man allerdings das Aufl eben der Sporen mit ihrer Entstehungsgeschichte, so zeigt sich, dass frühe Sporen schneller keimen und mit höherer Wahrscheinlichkeit auswachsen als späte Sporen. Weitere Experimente bestätigten, dass der Sporulationszeitpunkt -unabhän- Dehydrogenase -ein Enzym, das den Nährstoff und Keimungstrigger L-Alanin zu Pyruvat verstoffwechselt -beeinfl usst zumindest unter bestimmten Bedingungen die Sporenqualität in B. subtilis und das Auswachsen, aber nicht die Keimung [4,6]. Welche weiteren Qualitätsmerkmale einer Spore über den Sporulationszeitpunkt bestimmt werden und wie der Organismus die Sporenbildung beispielsweise über Zell-Zell-Kommunikation steuert [11], muss weiter untersucht werden.…”
Section: Der Lebenszyklus Im Zeitrafferunclassified
See 2 more Smart Citations